Prediction of parasitological cure in children infected with Trypanosoma cruzi using a novel multiplex serological approach: an observational, retrospective cohort study. Issue 8 (August 2021) - Jurado Medina, Laura; Chassaing, Emeric; Ballering, Griselda; Gonzalez, Nicolas; Marqué, Lola; Liehl, Peter; Pottel, Hans; de Boer, Jasper; Chatelain, Eric; Zrein, Maan; Altcheh, Jaime
Summary: Background: Assessment of therapeutic response with standard serological diagnostic assays in patients with chronic Chagas disease is a major challenge due to the long persistence of parasite-specific antibodies. The current consensus for parasitological cure is to monitor conversion from positive to negative Trypanosoma cruzi serology (seroreversion). However, because of robust humoral immune response, seroreversion by standard serological tests can take years to decades. Developing novel tests of parasitological cure or surrogates is thus a priority in the Chagas disease field. We aimed to evaluate the MultiCruzi assay as a predictive tool for parasitological cure in a cohort of treated infants and children with acute and chronic Chagas disease enrolled in a long-term retrospective longitudinal study with clinical, serological, and parasitological follow-up, and to explore whether MultiCruzi could predict parasitological cure more quickly than the current reference method. Methods: Patients from two retrospective paediatric Chagas disease cohort studies with clinical, serological, and parasitological follow-up, diagnosed and treated at the parasitology service, Hospital de Niños Ricardo Gutierrez (Buenos Aires, Argentina) were included in this retrospective cohort study. Serum samples were collected every 6 months to 12 months between Oct 22, 1990, and June 3, 2019, for cohort 1 and 1 month after birth for cohort 2 and then every 3 months for a year between July 23, 2012, and April 19, 2016. We evaluated serological follow-up with the Chagatest ELISA (Wiener Lab, Rosario, Argentina) and used this as a clinical reference method for the evaluation of seroreversion. We compared Chagatest ELISA results with results of MultiCruzi (InfYnity Biomarkers, Lyon, France), a novel antibody profiling multiplex assay, investigating seroreversion events with both of the assays and prediction of seroreversion with MultiCruzi using an interpretation formula. Findings: Combining experimental data from discrete analysis of 15 T cruzi antigens efficiently predicted seroreversion at an early stage, which was later confirmed by conventional T cruzi serology. In cohort 1 (n=69), which included children of three different age groups, we observed differences 2 years after therapy. In the 27 individuals from cohort 1 who were treated within the first 12 months of age, MultiCruzi predicted early seroreversion in 21 (78%) patients whereas nine (33%) patients showed seroreversion with Chagatest ELISA (seroreversion difference 0·44, 95% CI 0·26–0·63; p=0·0005). In the 12 patients from cohort 1 treated between 1 year and 2 years of age, MultiCruzi predicted early seroreversion in six (50%) patients, whereas only one (8%) patient was confirmed to be seronegative with Chagatest ELISA (seroreversion difference 0·42, 95% CI 0·14–0·70; p=0·0253). In the 30 patients from cohort 1 who were treated between 2 years and 19 years of age, MultiCruzi predicted early seroreversion in five (6%) patients, whereas no patients were found to be seronegative with Chagatest ELISA (seroreversion difference 0·17, 0·03–0·30; p=0·0253). In cohort 2 (n=27), which included only children younger than 1 year of age and had a shorter follow up (between 5 months and 32 months), the proportion of reported events was significantly different 180 days after treatment for the T cruzi -positive group (early seroreversion predicted in nine [90%] of ten patients with MultiCruzi and confirmed seroreversion in four [40%] of ten patients with Chagatest ELISA; seroreversion difference 0·50, 95% CI 0·19–0·81; p=0·0253) and for the T cruzi -negative group 90 days (early seroreversion predicted in five [29%] of 17 patients with MultiCruzi and confirmed seroreversion in one [6%] of 17 patients with Chagatest ELISA; seroreversion difference 0·24, 0·03–0·44; p=0·0455) and 180 days (early seroreversion predicted in 17 [100%] of 17 patients with MultiCruzi and confirmed seroreversion only in seven [41%] of 17 patients with Chagatest ELISA; seroreversion difference 0·59, 0·35–0·82; p=0·0016) after treatment. Interpretation: The MultiCruzi assay can be used as a predictive monitoring tool to assess parasitological cure in children. This approach might be a solution to forecast forthcoming seroreversion in treated adults infected with T cruzi, but this requires further investigation. Funding: Drugs for Neglected Diseases initiative. Translations: For the Spanish, Portuguese and French translations of the abstract see Supplementary Materials section.